BACTERIAL ISOLATION AND ANTIBIOGRAM STUDIES IN DOGS WITH OPEN AND CLOSED-CERVIX PYOMETRA - Nayana Devarajan; B. Bibin Becha; C. Jayakumar; M.P. Unnikrishnan; Syam K. Venugopal (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The emergence of antimicrobial resistance is raising public health concerns globally and random use of ineffective antibiotics in dogs creates great trouble during therapeutic interventions. Antibiogram determines the antibiotics to which a particular microorganism is susceptible, allowing clinicians to select the most effective treatment. This approach ensures use of antibiotics judiciously and in proper doses, helping to curb the development of resistant strains. Antibiogram studies were performed in 12 dogs affected with open and closed-cervix pyometra. Group I contained six dogs with open- cervix pyometra and Group II contained six dogs with closed-cervix pyometra. All the dogs were treated with mifepristone @ 2.5 mg/kg body weight twice daily for five days orally and from third day onwards, after ensuring the cervical patency, cloprostenol was administered @ 5 μg/kg body weight subcutaneously as once daily injection, on every third day, till complete emptying of uterus, as evaluated by ultrasonography. Bacterial isolation and antibiogram studies were carried out using sterile anterior vaginal swabs collected from the affected dogs on the day of presentation in Group I and once the discharge was started in Group II. Gram’s reaction revealed mixed isolates in eight out of 12 samples collected. Gram negative bacilli were the predominant isolate obtained from both the groups. On antibiogram studies, maximum sensitivity in Group I isolates was noticed to ceftriaxone-sulbactam (66.67%), followed by gentamicin (50%), amoxicillin clavulanic acid (50%), amoxicillin (33.33%), ciprofloxacin (33.33%), cefotaxime (33.33%), co- trimoxazole (33.33%), metronidazole (33.33%) and enrofloxacin (16.67%). Maximum sensitivity in Group II was noticed to amoxicillin- clavulanic acid and gentamicin (83.33%) followed by ciprofloxacin and metronidazole (50%), cefotaxime (33.33%), amoxicillin (16.67%), ceftriaxone-sulbactam (16.67%), co-trimoxazole (16.67%), enrofloxacin (16.67%).